2015
DOI: 10.4236/ojped.2015.54054
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Music Therapy on Social Skill Growth in Educable Intellectual Disability Boys

Abstract: Introduction: Social skills include the ability to establish interpersonal relationships with others in a way that is acceptable in terms of norms of society and it should be beneficial to society and have mutual interest. Method: Sample was taken from especial elementary school for educable intellectual disability children in Mashhad, Iran. The sample was boys between 9 -11 years. After the initial selection of students, they were randomly assigned to two groups of twenty (experimental and control groups). 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For the emotional component, many studies suggested that music therapy had a positive impact on the person with an intellectual disability, including a decrease in disruptive behaviours (Coyle, 2011; Hoyle & McKinney, 2015; Jaschke & Scherder, 2015; Kalgotra & Warwal, 2017; Savarimuthu & Bunnell, 2002; Urpi, 2016) and anxiety (Agheana, 2017; Hooper & Lindsay, 1990; Perry, 2003; Watson, 2016), increase in self‐esteem (Almeida et al, 2011; Coyle, 2011; Detzner, 1997; Hatampour et al, 2011; Humpal, 1991; Lewis, 2019; Moceviciene & Prudnikova, 2015; Rickson & Warren, 2018; Savarimuthu & Bunnell, 2002; Sooful et al, 2013; Wilson & MacDonald, 2019), and improved self‐expression and management of emotions (Cameron, 2017; Coyle, 2011; Graham, 2004; Savarimuthu & Bunnell, 2002; Staab &Dvorak, 2019; Tyas, 2010; Urpi, 2016). Beneficial outcomes for the development of social skills were also found in many studies (Agheana, 2017; Agrotou, 1994; Duffy & Fuller, 2000; Graham, 2004; Hashemian & Mohammadi, 2015; Hoyle &McKinney, 2015; Humpal, 1991; McLaughlin & Adler, 2015; Rickson & Warren, 2018; Surujlal, 2013). In addition, following their sessions, Almeida et al (2011) and Hatampour et al (2011) noted an improvement in collaboration, awareness of the ‘other’ and turn‐taking in interpersonal relationships.…”
Section: Resultsmentioning
confidence: 57%
“…For the emotional component, many studies suggested that music therapy had a positive impact on the person with an intellectual disability, including a decrease in disruptive behaviours (Coyle, 2011; Hoyle & McKinney, 2015; Jaschke & Scherder, 2015; Kalgotra & Warwal, 2017; Savarimuthu & Bunnell, 2002; Urpi, 2016) and anxiety (Agheana, 2017; Hooper & Lindsay, 1990; Perry, 2003; Watson, 2016), increase in self‐esteem (Almeida et al, 2011; Coyle, 2011; Detzner, 1997; Hatampour et al, 2011; Humpal, 1991; Lewis, 2019; Moceviciene & Prudnikova, 2015; Rickson & Warren, 2018; Savarimuthu & Bunnell, 2002; Sooful et al, 2013; Wilson & MacDonald, 2019), and improved self‐expression and management of emotions (Cameron, 2017; Coyle, 2011; Graham, 2004; Savarimuthu & Bunnell, 2002; Staab &Dvorak, 2019; Tyas, 2010; Urpi, 2016). Beneficial outcomes for the development of social skills were also found in many studies (Agheana, 2017; Agrotou, 1994; Duffy & Fuller, 2000; Graham, 2004; Hashemian & Mohammadi, 2015; Hoyle &McKinney, 2015; Humpal, 1991; McLaughlin & Adler, 2015; Rickson & Warren, 2018; Surujlal, 2013). In addition, following their sessions, Almeida et al (2011) and Hatampour et al (2011) noted an improvement in collaboration, awareness of the ‘other’ and turn‐taking in interpersonal relationships.…”
Section: Resultsmentioning
confidence: 57%